Utilization of Accounting Information Systems in the Business Sector - Aeni, Khotiatul; Muliadi, Lalu Ahmad; Wahyuda, Lalu Muhammad Asyrul; Damayanti, Sri (Business Management, 2025)
Work productivity is an important thing that must be implemented by every employee in a company or government. System integrity is very important to increase work productivity and develop automated business activities. One product that has been developed to support this is an accounting information system. Accounting information systems (AIS) are an integral part of modern business management. In the current digital era, the use of information technology has become a necessity in optimizing the efficiency and effectiveness of company operations. This article will discuss the use of accounting information systems in the business sector, with a focus on the use of AIS in accommodating company needs in terms of financial management and control